Semiótica de la Interacción Comunicativa en las Organizaciones (2019)
This article presents both a methodological and conceptual framework for a micro-researchcurrently being developed as part of the course Communicative Interaction in Organisations, ofthe Communicative Studies Area in the Humanities Department at EAFIT University.The activity that is being carried out focuses on the observation of communicative practices ofsome organisations (small, large, industrial, health area, etc). Once instruction on participant observation, dense description, category all ocation and notions relevant to the particularities of communicative actions in organisations has been conducted, a formal agreement is established with specific organisations, and the objective and methodology are explained to them.The observation period has a six-month duration (the academic term). During this period each team of three students visits the organisation five or six times. Next, open presentations of the experience are presented to community and members of the organisation, for a final written account of an analytic approximation to the facts described.